Bird Assemblage and Preference to Tengger Sacred Trees: Conservation insights from Tengger Tribe, Indonesia - Agung Sih Kurnianto; Živa Justinek; Purnomo Purnomo; Jati Batoro; Nia Kurniawan (Indonesian Journal of Environment and Sustainable Development, 2017)
We investigated the bird composition and preference at visiting the sacred figs (Ficus sp.) and its adjacent area in two villages of Tengger tribe: Ngadas and Poncokusumo, Malang, Indonesia. We applied the point count method and the sacred tree became the center of point count circle. We recorded 16154 individual birds in 35 days of observation, consisted of 46 species and 24 families. The bird composition composed of 362 predators, 9452 insectivores, 6029 omnivores, 278 nectarivores, and 33 frugivores. The observed bird were recorded utilizing seedling (652 individuals), sapling (3122 individuals), pole (3440 individuals), perching on a tree (2782 individuals), and flying overs (6158 individuals). Most of the insectivores were recorded flying over, where this character is owned by Cave Swiftlet. Figs, as an important component at the sacred area, provides many important component that could support the bird life and regeneration process. The presence of sacred tree also improving the relation between birds and plants, higher than those in the urban area or natural forest, and resulted a positive impact to the sustainable system of its surrounding agriculture.Keywords: Bird, fig, sacred area, Bromo Tengger Semeru